A thematic analysis of a survey of hospital chaplains on death by neurologic criteria. Issue 1 (2nd January 2023) - Kitamura, Elizabeth; Lewis, Ariane
Abstract: Introduction: Little is known about chaplains' views on brain death/death by neurologic criteria (BD/DNC). Thematic analysis of comments made by hospital chaplains about BD/DNC can illuminate their perspectives on working with patients, families, and interdisciplinary teams during assessment for BD/DNC. Materials and methods: In an electronic survey distributed to members of five chaplaincy organizations between February and July 2019, we elicited free-text comments about BD/DNC. We performed a thematic analysis of the comments. Results: Four themes were present: (1) definition of life and death, (2) respect with a subtheme of physician obligation, (3) collaboration with a subtheme of communication, and (4) education with a subtheme of scepticism. Conclusions: Hospital chaplains are essential members of the interdisciplinary team involved in BD/DNC evaluation. They aim to ensure the interaction between families and the interdisciplinary team at the boundary of life and death and the intersection between religion and medicine is respectful, collaborative, and educational.